Juridical Analysis of The Role of The Sea and Coast Guard in Improving Maritime Security and The Environment: Research Study at The Tanjung Uban Class II Marine and Coast Guard Base Office - Benyamin Ginting; Erniyanti Erniyanti; Darwis Anatami; Soerya Respationo (FKIP, Universitas Palangka Raya, 2024)
Maritime security and environmental protection in Indonesian waters, especially in Tanjung Uban, are strategic issues considering the high level of shipping activities and potential threats to marine ecosystems. This study focuses on the juridical analysis of the role of the Marine and Coast Guard Unit (KPLP) in improving maritime security and environmental protection, with a case study at the Tanjung Uban Class II Marine and Coast Guard Base. The purpose of this study is to evaluate the effectiveness of the implementation of the duties and functions of the KPLP based on the existing legal framework, identify the obstacles faced, and provide recommendations to improve the performance of the KPLP. The research method used is a qualitative approach with descriptive analysis, including document studies, field observations, and interviews with related parties. The results of the study show that although KPLP Tanjung Uban has a strong legal foundation, the implementation of their duties and functions is still not optimal. The main obstacles include limited resources such as adequate personnel and equipment, lack of continuous training which results in low personnel competence, and ineffective coordination with related agencies such as the Indonesian Navy and Bakamla. The low awareness and compliance with safety and environmental regulations among maritime industry players also exacerbates the situation. Based on these findings, this study provides several suggestions. For KPLP, an increase in the budget is needed for the procurement of resources and equipment, as well as continuous training for personnel. For the public, especially ship owners and other users of waters, it is important to increase awareness and compliance with maritime and environmental regulations through active participation in education and socialization programs. Meanwhile, the government must strengthen coordination between relevant agencies through the establishment of regular coordination forums and integrated information systems, to ensure better synergy in surveillance, law enforcement, and emergency response in the waters of Tanjung Uban. This research is expected to make a significant contribution to improving maritime security and environmental protection in Indonesia, as well as becoming a reference for the development of more effective policies and strategies in the management of water areas